Plan de mejoramiento empresarial diseño de un plan de sucesión del talento humano de la sociedad portuaria regional de Buenaventura S.A. (2013)
The work presented here, aims, design a succession plan for Human Resource Regional Port of Buenaventura SA, as a business improvement plan. The proposed research is framed within the context of human resources management, so it is important to first mention a concept that allows better understand which involves the administration of human talent. According Idalberto Chiavenato, is the set of policies and practices necessary to address the aspects of management positions related to people or human resources, including recruitment, selection, training, compensation and performance evaluation. A succession plan is a continuation of an orderly and planned person over another, with equal or superior characteristics. Succession plans are critical today, as no company can guarantee the permanence of its staff. Therefore, this improvement plan will serve as a planning tool to identify who could cover a certain position in one to two years and who over time, and what are the development plans we have put together to ensure that people are prepared . This research proposes an alternative based breeding box replacements ensure human talent in strategic positions (keys and / or critical) of the organization Regional Port of Buenaventura SA, allowing counteract the weaknesses in human resources that can be presented on arrival retirement of strategic positions, and face a globalized human resource and learning evolving.